(untitled) (Studia Prawnicze / The Legal Studies, 2023)
The subject of the article is about the most important problems of perfecting legal regulations, regulating the organization and the functioning of the scientific teams such as: scientific-research institutes, laboratories, construction and design and technological enterprises. Analysing the traditional structure of the organization of science which is based on the division of the scientific instututes into three systems: the academic, the educational and the department, the author stands for its reorganization by means of substituting the department institutes with the interdepartment ones. The assignment of the scientific department institutes to the State Committee of Science and Technology would discharge, according to the author, the ministries from the basic investigation work and would permit the Soviet Academy of Sciences wider possibilities of the technical elaboration and the implementation of new scientific ideas developed in the academic institutes. Moreover, the author points out the necessity of perfecting the planning and the scientific research financing systems and the functioning of the scientific information centres. He also stresses the necessity of creating the optimal and psychological climate in the scientific teams. To make the system of science and technology achievements implantation into the production more efficient, the authors fosters the project of the foundation of a special fund which would cover the eventual losses connected with the implantation of discoveries into the production. In the final part of the article the author postulates the elaboration of the ethic code of the scientific worker and the initiation of work on the scientific creation law, which would include the basic principles of the scientific policy of the state.